Zimowe spisy nietoperzy na Wyżynie Krakowskiej w latach 2018–2022 na tle historii badań - Nowak, Jakub; Grzywiński, Witold (Zenodo, 2022)
During 264 controls 8,680 bats were found, of which 8,652 were identified. Sixty-four caves were controlled at least once, and bats were found in 56 of them. The presence of at least 13 bat species was confirmed: Rhinolophus hipposideros, R. ferrumequinum, Myotis myotis, M. bechsteinii, M. nattereri,M. emarginatus, M. mystacinus/brandtii/alcathoe, M. dasycneme, M. daubentonii, Eptesicus nilssonii,E. serotinus, Plecotus auritus and Barbastella barbastellus . The most numerous species were R. hipposideros (71.6%), M. myotis (13.5%), M. emarginatus (6.8%), and B. barbastellus (4.2%). Over the past 35 years a distinct increase in the numbers of bats has been observed. The biggest increases concern R. hipposideros, M. emarginatus and B. barbastellus . After an increase from 2013 to 2017, the population of M. myotis remained stable during the next five years of research. The rare bat species R. ferrumequinum, M. bechsteinii , and E. nilssonii were noted. The most important sites are: Ciemna Cave, Nietoperzowa Cave, Racławicka Cave, Twarda Cave, Wierzchowska Górna Cave and Łokietka Cave.